Nano air filtering material and preparation method thereof
Nano-air filter materials prepared by using electrospun fibers loaded with brocade lantern extracts, the problem of bacteria breeding of air filter materials in closed environments is solved, and high-efficiency filtration and antibacterial effects of the whole life cycle are achieved under low filtration resistance.
Patent Information
- Application Number
- CN202411789601.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter materials, in particular to a nanometer air filter material and a preparation method thereof. Background Art
[0002] The air quality in a closed environment is closely related to the health and life safety of the group in that environment. There is a large flow of people in large closed environments such as large exhibition venues, hospitals, and stations. The air in large closed environments needs to be circulated through filtering equipment such as central air conditioners. If there are bacteria, viruses, and other pathogens that endanger human health lurking in the air, it will easily cause a potential threat of spread. Air filtration in a closed environment needs to be circulated through central air conditioning. Air filter materials used for a long time will also breed bacteria and cause secondary pollution of the air. The filtration efficiency of the filter material is its main indicator. In addition, the filtration resistance of the material significantly affects the operating noise and energy consumption. Therefore, there is an urgent need to provide an antibacterial high-filtration, low-resistance air filter material. Summary of the invention
[0003] In view of this, the present invention provides a nano air filter material, which has excellent antibacterial and antimicrobial properties and can achieve a high-efficiency filtering effect under a low filtering resistance state.
[0004] In order to achieve the above object, the present invention adopts the following technical solution:
[0005] In one aspect, the present invention provides a nanometer air filter material, wherein the nanometer air filter material is composed of electrospun fibers loaded with Lantern Festival extract;
[0006] The electrostatic spinning fiber loaded with Lantern Festival extract comprises the following components in percentage by mass: 1-50% of Lantern Festival extract and 50-99% of electrostatic spinning material.
[0007] Preferably, the Lantern Festival extract includes at least one of a Lantern Festival berry extract and a Lantern Festival calyx extract.
[0008] Preferably, the diameter of the electrospun fibers loaded with the P. quinquefolia extract is 100-1500 nm.
[0009] Preferably, the surface density of the nano air filter material is 0.05-4g / m 2 .
[0010] Preferably, the electrospinning material includes one or more of polyethylene oxide, polyvinyl alcohol, gelatin, polyurethane, polyacrylonitrile, polycaprolactone, polylactic acid, and polyvinylidene fluoride.
[0011] On the other hand, the present invention also provides a method for preparing the nano air filter material described in any one of the above, comprising the following steps:
[0012] (1) dissolving the Lantern Festival extract in a first solvent to obtain a first spinning solution;
[0013] (2) dissolving the electrospinning material in a second solvent to obtain a second spinning solution;
[0014] (3) mixing the first spinning solution and the second spinning solution to obtain a mixed spinning solution;
[0015] (4) The mixed spinning solution is sprayed onto a release paper roll by an electrostatic spinning machine, and separated from the release paper after curing to obtain a nano air filter material.
[0016] Preferably, the mass content of the Lantern Festival extract in the first spinning solution is 5-30%.
[0017] Preferably, the mass content of the electrospinning material in the second spinning solution is 5-35%.
[0018] Preferably, the viscosity of the second spinning solution is 0.5-10 Pa·s.
[0019] Preferably, the Lantern Festival extract is in powder form with a purity of ≥95%.
[0020] Preferably, the first solvent includes one or more of methanol, ethanol, acetone, dichloromethane, dimethylformamide, and dimethylacetamide.
[0021] Preferably, the second solvent includes one or more of methanol, ethanol, acetone, chloroform, dimethylformamide, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide.
[0022] Preferably, the conditions for electrospinning in the electrospinning machine in step (4) are as follows: the high voltage electric field voltage is 25-60 kV, the receiving distance is 15-40 cm, and the reciprocating motion speed of the spinning block is 0.5-12 m / s.
[0023] The nanometer air filter material of the embodiment of the present invention has the following beneficial effects compared with the prior art:
[0024] The nanometer air filter material of the present invention uses Lantern Festival extract as the antibacterial component, which is evenly mixed into the electrospinning material, and a nanometer fiber air filter material with significant antibacterial effect, high filtration efficiency and low filtration resistance is prepared by electrospinning, which can be widely used in air filters in closed environments. DETAILED DESCRIPTION
[0025] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0026] In one aspect of the present invention, the present invention proposes a nano air filter material, the nano air filter material is composed of electrostatic spinning fibers loaded with Lantern Festival extract; the electrostatic spinning fibers loaded with Lantern Festival extract include the following components in percentage by mass: Lantern Festival extract 1-50%, electrostatic spinning material 50-99%. The mass percentage of Lantern Festival extract can be 1%, 5%, 10%, 20%, 30%, 40%, 50%, etc., and the mass percentage of electrostatic spinning material can be 99%, 95%, 90%, 80%, 70%, 60%, 50%, etc. The higher the content of Lantern Festival extract, the better the antibacterial and antibacterial effect. Specifically, if the content of Lantern Festival extract is less than 5%, it only has an antibacterial effect, and the function of inhibiting bacterial reproduction and regeneration will be significantly reduced. In addition, as the content of Lantern Festival extract increases, the strength of the electrostatic spinning fiber loaded with Lantern Festival extract will be lower. If the content of Lantern Festival extract exceeds 50%, it is not easy to form continuous fibers.
[0027] Lantern Festival grows naturally in Northeast my country and its berries are edible. Lantern Festival extract has significant antibacterial effect on Escherichia coli, Staphylococcus aureus, Salmonella and Bacillus subtilis. The present invention uses Lantern Festival extract as an antibacterial component, mixes it evenly into an electrospinning material, and prepares a nanofiber air filter material with significant antibacterial effect, high filtration efficiency and low filtration resistance through electrospinning, which can be widely used in air filters in closed environments.
[0028] In some embodiments of the present invention, the Lantern Festival extract includes at least one of the Lantern Festival berry extract and the Lantern Festival calyx extract. The Lantern Festival extract used in the present invention is mainly obtained by extraction and purification from natural Lantern Festival berries and calyx, which is green and environmentally friendly, and the algin and flavonoids contained in the extract have good antibacterial and anti-inflammatory activities.
[0029] In some embodiments of the present invention, the diameter of the electrospun fiber loaded with Lantern Festival extract is 100-1500nm, for example, it can be 100nm, 200nm, 300nm, 500nm, 800nm, 1000nm, 1200nm, 1500nm, etc. Among them, within the range of 100-1500nm, the smaller the diameter of the electrospun fiber loaded with Lantern Festival extract, the higher the filtration efficiency and the greater the filtration resistance, but when it is less than 100nm, the filtration resistance is too large, so the present invention limits the diameter of the electrospun fiber loaded with Lantern Festival extract to 100-1500nm.
[0030] In some embodiments of the present invention, the surface density of the nano air filter material is 0.05-4 g / m 2 , preferably 0.5-2.0g / m 2 , for example, it can be 0.05g / m 2 , 0.1g / m 2 , 0.5g / m 2 , 1g / m 2 , 1.5g / m 2 , 2g / m 2 , 2.5g / m 2 , 3g / m 2 3.5g / m 2 , 4g / m 2 The nanometer air filter material has a better combination of filtration resistance and filtration efficiency within this surface density range. When the filtration resistance is lower than 20Pa, the filtration efficiency for 0.01-0.3um oily dioctyl phthalate (DOP) particles and salt particles such as NaCl is more than 95%, and it has significant antibacterial and antimicrobial effects on Escherichia coli, Staphylococcus aureus, Salmonella, etc.
[0031] In some embodiments of the present invention, the electrospinning material includes one or more of polyethylene oxide, polyvinyl alcohol, gelatin, polyurethane, polyacrylonitrile, polycaprolactone, polylactic acid, and polyvinylidene fluoride.
[0032] The nanometer air filter material of the present invention has the characteristics of large specific surface area, strong adsorption effect and low cost. It has antibacterial and antimicrobial effect throughout its life cycle, can effectively prevent secondary air pollution caused by bacteria breeding on the filter material, and can achieve high-efficiency filtration effect under low filtration resistance state. The filtration resistance is less than 20Pa, and the filtration efficiency for oily DOP particles of 0.01-0.3um and saline NaCl and KCl particles is 95%-100%.
[0033] In another aspect of the present invention, the present invention provides a method for preparing the nano air filter material described in any one of the above, comprising the following steps:
[0034] (1) Dissolving the Lantern Festival extract in a first solvent to obtain a first spinning solution.
[0035] In this step, the dissolving is stirring at room temperature until dissolved, and the mass content of the Lantern Festival extract in the first spinning solution is 5-30%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, etc. Preferably, the first solvent includes one or more of methanol, ethanol, acetone, dichloromethane, dimethylformamide, and dimethylacetamide. The mass content of Lantern Festival extract is lower than 5%, and the antibacterial effect is not obvious. As the content of Lantern Festival extract increases, the antibacterial and antibacterial effects increase significantly. The higher the content of Lantern Festival extract, the lower the strength of the nanofibers, and it is not suitable to form continuous nanofibers when it exceeds 50%.
[0036] In some embodiments of the present invention, the Lantern Festival extract is in powder form with a purity ≥ 95%, for example, it can be 95%, 96%, 97%, 98%, 99%, etc. If the purity is too low, the content of antibacterial components in the Lantern Festival extract will be reduced, affecting the antibacterial effect.
[0037] In some embodiments of the present invention, in order to improve the dissolution efficiency, the particle size of the Lantern Festival extract is ≤2 μm, wherein the particle size may be, for example, 2 μm, 1.5 μm, 1 μm, 0.5 μm, 0.05 μm, 0.01 μm, etc., without any particular limitation.
[0038] (2) Dissolving the electrospinning material in a second solvent to obtain a second spinning solution.
[0039] In this step, the dissolution is carried out at 25-90°C and stirring is continued for 2-24 hours. The specific dissolution temperature and stirring time can be adjusted routinely according to the actual situation. Generally speaking, the dissolution temperature cannot exceed the boiling point of the solvent, and the stirring time is necessary for the electrospinning material to be completely dissolved and spinnable.
[0040] In some embodiments of the present invention, the mass content of the electrospinning material in the second spinning solution is 5-35%, for example, it can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, etc. If the mass content of the electrospinning material in the second spinning solution is too low, it will affect the mechanical properties such as the strength of the fiber; the viscosity of the second spinning solution is 0.5-10Pa·s, for example, it can be 0.5Pa·s, 1Pa·s, 2Pa·s, 3Pa·s, 4Pa·s, 5Pa·s, 6Pa·s, 7Pa·s, 8Pa·s, 9Pa·s, 10Pa·s, etc. If the viscosity is too low, it cannot form a fiber, and if the viscosity is too high, the spinning process cannot be carried out. Preferably, the second solvent includes one or more of methanol, ethanol, acetone, chloroform, dimethylformamide, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide.
[0041] (3) Mixing the first spinning solution and the second spinning solution to obtain a mixed spinning solution, and temporarily storing the mixed spinning solution in a solution storage barrel.
[0042] In this step, the solution is dissolved at 25-90°C and stirred continuously until it is evenly mixed, wherein the dissolving temperature should not exceed the boiling point of the solvent. After evenly mixing, it is subjected to defoaming treatment to obtain a mixed spinning solution. The specific dissolving temperature, stirring time and defoaming treatment can be routinely adjusted according to actual conditions and are not specifically limited.
[0043] (4) The mixed spinning solution is sprayed onto a release paper roll by an electrostatic spinning machine, and separated from the release paper after curing to obtain a nano air filter material.
[0044] In this step, the electrospinning machine is a needle-free electrospinning machine, and the parameters of the electrospinning process meet the following conditions: the high-voltage electric field voltage is 25-60kV, the receiving distance is 15-40cm, the reciprocating motion speed of the spinning block is 0.5-12m / s, and the release paper transmission speed is 0.2-20m / s. The spinning block is reciprocating to evenly coat the spinning solution on each spinning line, and the spinning solution is rapidly and vertically sprayed from the spinning line to the release paper through the high-voltage electric field between the spinning line and the release paper. The present invention does not specifically limit the specific spinning method, and conventional steps can be used.
[0045] The high voltage electric field voltage can be, for example, 25kV, 30kV, 40kV, 50kV, 60kV, etc., the receiving distance is 15cm, 20cm, 25cm, 30cm, 35cm, 40cm, etc., the reciprocating speed of the spinning block is 0.5m / s, 1m / s, 2m / s, 5m / s, 7m / s, 8m / s, 10m / s, 12m / s, etc., the release paper transmission speed is 0.2m / s, 0.5m / s, 1m / s, 2m / s, 5m / s, 7m / s, 8m / s, 10m / s, 15m / s, 20m / s, etc., the number of spinning lines is mainly based on the setting of the electrospinning machine, usually 10-30 lines are set, and the limitation of the spinning parameters in the present invention is also based on the number of 10-30 spinning lines. The more the number of spinning lines, the faster the overall spinning speed, and the required spinning voltage is also correspondingly increased.
[0046] In some embodiments of the present invention, the curing treatment is drying at 60-90°C for 5-30 minutes, wherein the drying temperature is determined according to the boiling point of the solvent and can be slightly higher than the boiling point of the solvent, and the drying time is terminated when the electrospinning solvent is completely evaporated. For example, it can be dried at 60°C for 30 minutes, at 80°C for 10 minutes, at 90°C for 5 minutes, etc. The specific drying temperature and time can be conventionally adjusted according to actual conditions.
[0047] The present invention uses a needleless electrospinning method to apply a mixed spinning solution on an electrospinning line, and directly sprays the spinning solution onto a release paper under the action of a high-voltage electric field, and then peels off the release paper after drying, so as to prepare a nano air filter material. The preparation method is simple, the production efficiency is high, and large-scale production can be achieved.
[0048] Example 1
[0049] This embodiment provides a nanometer air filter material, and the preparation method is as follows:
[0050] (1) dissolving a Pleurotus eryngii berry extract having a particle size of 1.5 μm and a purity of 95% in a mixed solvent of ethanol:methanol=3:1 to obtain a Pleurotus eryngii (PL) solution having a mass content of 8%;
[0051] (2) dissolving polyvinyl alcohol powder in a mixed solvent of ethanol and methanol in a ratio of 3:1, and stirring continuously at 25° C. for 3 h to obtain a PVA solution with a mass content of 12% and a viscosity of 3.5 Pa·s;
[0052] (3) Mixing the brocade lantern solution and the PVA solution in a ratio of 1:9 at 25° C. and stirring continuously to obtain a PVA / PL spinning solution after defoaming;
[0053] (4) PVA / PL spinning stock solution was added into the liquid reservoir, and under the action of the 35 kV high voltage electric field of the needle-free electrospinning machine, it was directly vertically sprayed and received onto the release paper roll transmitted online. The receiving distance was 20 cm, and the reciprocating speed of the spinning block was 3.5 m / s. After the electrospinning process was completed, it was immediately transported to the oven and dried at 70 ° C for 10 min, and then peeled off from the release paper to obtain a nano air filter material with an average fiber diameter of 800 nm.
[0054] The surface density of the nanometer air filter material prepared in this example is 1.1 g / m 2 Using TSI8130 automatic air filtration tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl was tested to be 99.8%, with a filtration resistance of 15.4Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 96.7%, with a filtration resistance of 16.1Pa. According to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, multiple bacterial species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli were tested and there were no obvious colonies. The antibacterial rate reached 80%, and the antibacterial and antibacterial effects were excellent.
[0055] Example 2
[0056] This embodiment provides a nanometer air filter material, and the preparation method is as follows:
[0057] (1) dissolving a Lanterna calyx extract with a particle size of 1.2 μm and a purity of 98% in a solvent (dimethylacetamide:acetone=4:1) to obtain a Lanterna calyx extract with a mass content of 6%;
[0058] (2) dissolving polycaprolactone powder in a solvent (dimethylacetamide:acetone=4:1), stirring continuously at 70° C. for 6 h, and obtaining a polycaprolactone solution with a mass content of 12% and a viscosity of 3.8 Pa·s;
[0059] (3) mixing the brocade lantern solution and the polycaprolactone solution at a ratio of 2:8 at 75° C. and stirring continuously to obtain a PCL / PL spinning solution after defoaming;
[0060] (4) The PCL / PL spinning stock solution was added into the liquid reservoir, and under the action of the 35 kV high voltage electric field of the needle-free electrospinning machine, it was directly sprayed and received onto the release paper roll transmitted online. The receiving distance was 20 cm, and the reciprocating speed of the spinning block was 4.8 m / s. After the electrospinning process was completed, it was immediately transported into the oven and dried at 80 ° C for 10 min, and then separated from the release paper to obtain a nano air filter material with an average fiber diameter of 650 nm.
[0061] The surface density of the nanometer air filter material prepared in this embodiment is 1.2 g / m 2 Using TSI 8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl was tested to be 99.93%, with a filtration resistance of 18.4Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 97.3%, with a filtration resistance of 17.1Pa. According to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, multiple bacterial species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli were tested and there were no obvious colonies. The antibacterial rate reached 85%, with excellent antibacterial effect.
[0062] Example 3
[0063] This embodiment provides a nanometer air filter material, and the preparation method is as follows:
[0064] (1) dissolving a Lanterna calyx extract with a particle size of 2 μm and a purity of 95% in an N,N-dimethylformamide solvent to obtain a Lanterna calyx (PL) solution with a mass content of 9%;
[0065] (2) dissolving polylactic acid powder in N,N-dimethylformamide solvent and stirring at 35° C. for 2 h to obtain a PLA solution with a mass content of 11% and a viscosity of 4.2 Pa·s;
[0066] (3) mixing the brocade lantern solution and the PLA solution in a ratio of 2:8 at 25° C., stirring and mixing evenly, and defoaming to obtain a PLA / PL spinning solution;
[0067] (4) The PLA / PL spinning stock solution was added into the liquid reservoir, and under the action of the 45 kV high voltage electric field of the needleless electrospinning machine, it was directly sprayed and received onto the release paper roll transmitted online. The receiving distance was 18 cm, and the reciprocating speed of the spinning block was 5.5 m / s. After the electrospinning process was completed, it was immediately transported into the oven and dried at 65 ° C for 15 min, and then peeled off from the release paper to obtain a nano air filter material with an average fiber diameter of 750 nm.
[0068] The surface density of the nanometer air filter material prepared in this embodiment is 1.8 g / m 2 Using TSI8130 automatic air filtration tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl was tested to be 96.4%, with a filtration resistance of 19.5Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 95.3%, with a filtration resistance of 18.2Pa. According to the oscillation test method in ASTM E2149 and GB / T20944.2-2008 standards, multiple bacterial species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli were tested and there were no obvious colonies. The antibacterial rate reached 85%, with excellent antibacterial effect.
[0069] Example 4
[0070] This embodiment provides a nanometer air filter material, and the preparation method is as follows:
[0071] (1) dissolving a Pleurotus eryngii berry extract having a particle size of 1.8 μm and a purity of 98% in a solvent of dimethylacetamide: dimethyl sulfoxide = 3:1 to obtain a Pleurotus eryngii (PL) solution having a mass content of 10%;
[0072] (2) dissolving polyoxyethylene powder in a solvent of dimethylacetamide: dimethyl sulfoxide = 3:1, stirring continuously at 25° C. for 3.5 h, to obtain a PEO solution with a mass content of 11% and a viscosity of 3.8 Pa·s;
[0073] (3) mixing the brocade lantern solution and the PEO solution at a ratio of 3:7 at 60° C. with continuous stirring and mixing, and obtaining the PEO / PL spinning stock solution after defoaming;
[0074] (4) PEO / PL spinning stock solution was added into the liquid reservoir, and under the action of the 45 kV high voltage electric field of the needle-free electrospinning machine, it was directly sprayed and received onto the release paper roll transmitted online. The receiving distance was 15 cm, and the reciprocating speed of the spinning block was 2.6 m / s. After the electrospinning process was completed, it was immediately transported to the oven and dried at 60 ° C for 15 min, and then peeled off from the release paper to obtain a nano air filter material with an average fiber diameter of 550 nm.
[0075] The surface density of the nanometer air filter material prepared in this example is 1.0 g / m 2 Using TSI 8130 automatic air filter tester, at an aerosol flow rate of 32cm / s, the filtration efficiency of 0.075um saline NaCl was tested to be 96.29%, with a filtration resistance of 15.8Pa. The filtration efficiency of 0.08-2.5um DOP oily particles can reach more than 99.95%, with a filtration resistance of 16.3Pa. According to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, multiple bacterial species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli were tested and there were no obvious colonies. The antibacterial rate reached 89.6%, with excellent antibacterial effect.
[0076] Example 5
[0077] This embodiment is basically the same as Embodiment 1, and the only difference is that some parameters of step (3) and step (4) are different.
[0078] (3) mixing the brocade lantern solution and the PVA solution in a ratio of 3:7 at 25° C., stirring and mixing evenly, and obtaining the PVA / PL spinning stock solution after defoaming;
[0079] (4) PVA / PL spinning stock solution was added into the liquid reservoir, and under the action of the 45 kV high voltage electric field of the needle-free electrospinning machine, it was directly vertically sprayed and received onto the release paper roll transmitted online. The receiving distance was 21 cm, and the reciprocating speed of the spinning block was 4.5 m / s. After the electrospinning process was completed, it was immediately transported to the oven and dried at 70 ° C for 10 min, and then peeled off from the release paper to obtain a nano air filter material with an average fiber diameter of 600 nm.
[0080] The surface density of the nanometer air filter material prepared in this embodiment is 0.9 g / m 2, using TSI8130 automatic air filtration tester, at an aerosol flow rate of 32cm / s, tested 0.075um, the saline NaCl filtration efficiency is 99.64%, the filtration resistance is 19.6Pa, the filtration efficiency of 0.08-2.5um DOP oily particles can reach 98.3%, and the filtration resistance is 16.4Pa; according to the oscillation test method in ASTME2149 and GB / T 20944.2-2008 standards, the tests of Staphylococcus aureus negative, Staphylococcus aureus positive, Escherichia coli and other bacteria showed no obvious colonies, the antibacterial rate reached 88%, and the antibacterial effect is even better.
[0081] Example 6
[0082] This embodiment is basically the same as Embodiment 2, the only difference being that some parameters of step (3) and step (4) are different.
[0083] (3) mixing the brocade lantern solution and the polycaprolactone solution at a ratio of 4:6 at 75° C., stirring and mixing evenly, and obtaining the PCL / PL spinning stock solution after defoaming;
[0084] (4) The PCL / PL spinning stock solution was added into the liquid reservoir, and under the action of the 50 kV high voltage electric field of the needle-free electrospinning machine, it was directly sprayed and received onto the release paper roll transmitted online. The receiving distance was 18 cm, and the reciprocating speed of the spinning block was 5.5 m / s. After the electrospinning process was completed, it was immediately transported into the oven and dried at 80 ° C for 10 min, and then separated from the release paper to obtain a nano air filter material with an average fiber diameter of 500 nm.
[0085] The surface density of the nanometer air filter material prepared in this example is 1.0 g / m 2 , using TSI8130 automatic air filtration tester, at an aerosol flow rate of 32cm / s, tested 0.075um, the saline NaCl filtration efficiency is 99.96%, the filtration resistance is 19.98Pa, the filtration efficiency of 0.08-2.5um DOP oily particles can reach 99.3%, and the filtration resistance is 18.7Pa; according to the oscillation test method in ASTM E2149 and GB / T 20944.2-2008 standards, the tests of Staphylococcus aureus negative, Staphylococcus aureus positive, Escherichia coli and other bacteria showed no obvious colonies, the antibacterial rate reached 90%, and the antibacterial effect is even better.
[0086] Comparative Example 1
[0087] This comparative example is basically the same as Example 1, with the only difference being that in step (1), the concentration of the Lantern Festival berry extract is 80%, and the mass content of the Lantern Festival solution is 3%.
[0088] The nanometer air filter material prepared in this comparative example was tested by the oscillation test method in ASTM E2149 and GB / T20944.2-2008 standards for multiple bacterial species such as Staphylococcus aureus negative, Staphylococcus aureus positive, and Escherichia coli, and obvious colonies were found, with an antibacterial rate of 67.1%, and the antibacterial and antibacterial effects were poor.
[0089] Comparative Example 2
[0090] This comparative example is basically the same as Example 1, with the only difference being that in step (2), a PVA solution with a mass content of 40% and a viscosity of 10.4 Pa·s is prepared.
[0091] The nanometer air filter material fiber prepared in this comparative example is difficult to form continuous fibers by spinning. Further increasing the spinning voltage to 55KV and the receiving distance to 40cm still cannot obtain an effective fiber layer.
[0092] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A nanometer air filter material, characterized in that: The nanometer air filter material is composed of electrostatically spun fibers loaded with Lantern Festival extract; The electrostatic spinning fiber loaded with Lantern Festival extract comprises the following components in percentage by mass: 1-50% of Lantern Festival extract and 50-99% of electrostatic spinning material.
2. The nanometer air filter material according to claim 1, characterized in that: The Lantern Festival extract includes at least one of a Lantern Festival berry extract and a Lantern Festival calyx extract.
3. The nanometer air filter material according to claim 1, characterized in that: The diameter of the electrospun fiber loaded with the Lantern Festival extract is 100-1500nm.
4. The nanometer air filter material according to claim 1, characterized in that: The surface density of the nanometer air filter material is 0.05-4g / m 2 .
5. The nanometer air filter material according to claim 1, characterized in that: The electrospinning material includes one or more of polyoxyethylene, polyvinyl alcohol, gelatin, polyurethane, polyacrylonitrile, polycaprolactone, polylactic acid, and polyvinylidene fluoride.
6. A method for preparing the nanometer air filter material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) dissolving the Lantern Festival extract in a first solvent to obtain a first spinning solution; (2) dissolving the electrospinning material in a second solvent to obtain a second spinning solution; (3) mixing the first spinning solution and the second spinning solution to obtain a mixed spinning solution; (4) The mixed spinning solution is sprayed onto a release paper roll by an electrostatic spinning machine, and separated from the release paper after curing to obtain a nano air filter material.
7. The method for preparing the nanometer air filter material according to claim 6, characterized in that: The mass content of Lantern Festival extract in the first spinning solution is 5-30%; The Lantern Festival extract is in powder form with a purity of ≥95%.
8. The method for preparing the nanometer air filter material according to claim 6, characterized in that: The mass content of the electrospinning material in the second spinning solution is 5-35%; The viscosity of the second spinning solution is 0.5-10 Pa·s.
9. The method for preparing the nanometer air filter material according to claim 6, characterized in that: The first solvent includes one or more of methanol, ethanol, acetone, dichloromethane, dimethylformamide, and dimethylacetamide; The second solvent includes one or more of methanol, ethanol, acetone, chloroform, dimethylformamide, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide.
10. The method for preparing the nanometer air filter material according to any one of claims 7 to 9, characterized in that: The conditions for electrospinning in the electrospinning machine in step (4) are as follows: the high voltage electric field voltage is 25-60 kV, the receiving distance is 15-40 cm, and the reciprocating motion speed of the spinning block is 0.5-12 m / s.
Citation Information
Patent Citations
Spinning solution and method for preparing antibacterial air filtering membrane by spinning solution
CN104213202A
Efficient low-resistance antibacterial filtering material containing bamboo leaf flavonoids and preparation method and application of efficient low-resistance antibacterial filtering material
CN105999859A
Functional air filtering material
CN107261865A
Electrospun composition
JP2008255555A
Filter element
WO2020142002A1